Langkah Mempercepat Perkembangan Kurikulum Merdeka Belajar - I Komang Wahyu Wiguna; Made Adi Nugraha Tristaningrat (STAHN Mpu Kuturan Singaraja, 2022)
This study was conducted to gather sufficient information on the Steps to Accelerate the Development of the Merdeka Belajar Curriculum. The method used in this study is through a literature study that collects several previous studies and existing policies from the government to answer steps to accelerate the development of a merdeka belajar curriculum. The results of this study indicate the need for an increase in qualified and competitive human resources. The next step is a mental revolution by increasing the promotion and preservation of culture to strengthen character and strengthen national identity. In addition, updating learning facilities and infrastructure is also a mandatory task carried out by educational institution managers for the better learning process.